Female labor force participation in Latin America: evidence of deceleration - Gasparini, Leonardo Carlos (2014)
This paper documents changes in female labor force participation (LFP) in Latin America exploiting a large database of microdata from household surveys of 15 countries in the period 1992-2012. We find evidence for a significant deceleration in the rate of increase of female LFP in the 2000s, breaking the marked increasing pattern that characterized the region for at least 50 years. The paper documents and characterizes this fact and examines various factors that could be driving the deceleration. Through a set of simple decompositions the paper helps to disentangle whether the patterns in female LFP are mainly accounted for by changes in the distribution of some direct determinants of the labor supply decision (e.g. education), or instead they are chiefly the consequence of some more profound transformation in behavior.